Evaluasi Layanan Perpustakaan Di SMP Negeri Karang Dapo - Elmiana (Manajer Pendididikan, 2023)
- The purpose of this study was to evaluate the implementation of services in the Karang Dapo State Middle School library. This research is an evaluation research with a qualitative descriptive method. One of the evaluation models that will be used in this study is the discrepancy evaluation model (DEM) or the inequality model. The research subject is the Head of Libraries, Librarians. Data collection techniques interview, observation, and documentation. The results of research on circulation services at the Karang Dapo Public Middle School Library apply member registration services, borrowing and returning books, rules, and making circulation statistics. The results of the assessment with the national library standard found that the reporting and maintenance aspects had been implemented while the collection management aspects had not been implemented in accordance with (SNP). On the results of the evaluation of reference services in the library, the service provides information and provides assistance in searching collections. The implementation of reader services related to facilities and infrastructure applies to aspects of the building, location, storage furniture and other equipment. Meanwhile, those who have not implemented national library standards are in the area aspect, work furniture and media equipment.